Intellectual Capital and Firm Performance: The Role of Institutional and Family Ownership - Bima Cinintya Pratama; Maulida Nurul Innayah (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2019)
Intellectual Capital (IC) is important because firms in Indonesia needs a lot of competitive advantage, mainly from IC, in order to compete in the era of ASEAN Economics Community (AEC). This study investigates the positive relationship between intellectual capital and firm performance and examine the moderating role of family ownership and institutional ownership on the relationship between intellectual capital and firm performance. The data collected from annual report from high-tech industries and conducted in Indonesia. The final sample used in this study consists of a total of 144 observations. This study uses panel data regression model analysis, i.e. fixed effect regression and random effect regression. The results showed that intellectual capital has a positive effect on financial performance in Indonesia. This result indicate that intellectual capital can give higher financial performance for the firms. On the other hand, the result found that the positive moderating role of family ownership and institutional ownership on the relationship between IC and firm financial performance.Keywords: Intellectual Capital, Family Ownership, Institutional Ownership, Financial Performance.